Diversity and Inclusion in Global Higher Education: Lessons from Across Asia - Mao, Jing (Journal of International Students, 2021)
Amid internationalization in higher education, modern classrooms have become diversified, which provides both opportunities and challenges for educators and institutions. In response to changing trends and transformative developments in Asian higher education, the editors of Diversity and Inclusion in Global Higher Education: Lessons from Across Asia argue that classroom diversity can deepen students’ learning potential when adequately harnessed and matched with inclusive pedagogy. This edited volume of contributions provides rich insights and practical strategies for cultivating diversity and inclusion in diverse settings in Asia and beyond.